Computational and experimental investigation of particulate matter deposition in cerebral side aneurysms. Issue 169 (26th August 2020) - Epshtein, Mark; Korin, Netanel
Abstract : Intracranial aneurysms frequently develop blood clots, plaque and inflammations, which are linked to enhanced particulate mass deposition. In this work, we propose a computational model for particulate deposition, that accounts for the influence of field forces, such as gravity and electrostatics, which produce an additional flux of particles perpendicular to the fluid motion and towards the wall. This field-mediated flux can significantly enhance particle deposition in low-shear environments, such as in aneurysm cavities. Experimental investigation of particle deposition patterns in in vitro models of side aneurysms, demonstrated the ability of the model to predict enhanced particle adhesion at these sites. Our results showed a significant influence of gravity and electrostatic forces (greater than 10%), indicating that the additional terms presented in our models may be necessary for modelling a wide range of physiological flow conditions and not only for ultra-low shear regions. Spatial differences between the computational model and the experimental results suggested that additional transport and fluidic mechanisms affect the deposition pattern within aneurysms. Taken together, the presented findings may enhance our understanding of pathological deposition processes at cardiovascular disease sites, and facilitate rational design and optimization of cardiovascular particulate drug carriers.